Verbs in English and Uzbek Semantic Typology - Оллаберганова Муборак Холмуратовна (Scientific Trends, 2024)
The article studies the place of the verb in word classes, its features, expression, forms, meanings, morphological categories, usage of verb types in both languages, as well as their typological and pragmatic features. It also reveals the similarities and differences between them in the languages being compared (English and Uzbek).
Keywords: Typology, verb types, morphological category, semantic typology, classification.